Deviation in Robert Browning's My Last Duchess: A Stylistic Study: Types of Deviation - Shihab, Teeba; Afrawi, Shouq Ali (Thi Qar Arts Journal, 2024)
This paper deals with the effects of deviation as a Stylistic device on the discourse of poetry by making it complex and ambiguous. This study aims at providing a theoretical side about deviation and its types.As well as providing, a practical side about an analysis of Robert Browning's My Last Duchess. It is hypothesized that Robert Browning poetry is affected by a set of deviations in order to make it unique and ambiguous.It is hoped that the paper will be valuable to both stylistic researchers end English language learners.The paper consists of an abstract and three chapters. The first chapter contains the procedure and the general framework that the paper is built on such as the problem, the hypothesis, the aimsand the model etc… .As for the second chapter it is devoted to discuss the literature review and to elaborate the model of analysis. Moreover, Chapter three is dedicated to the analysis of the paper. The paper ends withsome conclusions, an appendix and a bibliography.  It is concluded that poetry discourse is full of deviation and that kind of deviation marks it as difficult to be understandable straightforwardly. Furthermore, Robert Browning's Poetry is an exemplification of that type of deviation.